Acute Hemorrhagic Edema of Infancy: an unusual diagnosis for the general pediatrician - Diego Fontana Siqueira Cunha; Ana Letícia Fornazieri Darcie; Gabriel Nuncio Benevides; Angela Espósito Ferronato; Noely Hein; Denise Swei Lo; Cristina Ryoka Miyao Yoshioka; Maki Hirose; Débora Morais Cardoso; Alfredo Elias Gilio (University of São Paulo, 2015)
Acute Hemorrhagic Edema of Infancy (AHEI) is a rare leukocytoclastic vasculitis, clinically characterized by the classical triad: palpable purpuric skin lesions, edema and fever, and is commonly misdiagnosed as Henoch-Schönlein purpura. In addition to its sudden onset, AHEI is also characterized by its self-limited course with complete and spontaneous recovery occurring between 1 and 3 weeks. Because of the scarcity of studies on therapy with corticosteroids, the conservative approach is usually recommended. The authors report an unusual case of an one-year-old boy who presented with typical cutaneous rash of AHEI and orchitis, the latter showing complete resolution after less than 24 hours of prednisolone therapy. The authors call attention to this entity mainly as a differential diagnosis of Henoch-Schönlein purpura and to the importance of new studies to establish the benefits of corticosteroid therapy for AHEI.